Sarcoma esophagus: A case report and review of literature - Deshmukh, Jayashree; Sancheti, Sankalp; Dora, Tapas Kumar; Chatterjee, Abhishek; Das, Abhijit; Kapoor, Rakesh (Indian Journal of Case Reports, 2020)
Synovial sarcoma (SS) is an uncommon mesenchymal malignant neoplasm that occurs mainly in extremities. Sarcoma of the esophagus is a rare neoplasm and comprises 0.1–1.5% of all esophageal tumors. Only a few cases have been reported from the Indian context. We report a case of SS occurring in the esophagus of a 35-year-old male and managed with radical radiotherapy alone. We also want to highlight the histopathological and immunohistochemistry profile which aid in its accurate diagnosis. Molecular testing for SS18-SSX was done for confirmation.